The Influence of Electronic Commerce on International Trade and Development Strategy (Asian Business Research, 2022)
Since the 21st century, the rapid development of e-commerce and its application in the field of international trade have greatly impacted the original basic structure of international trade. E-commerce is like a double-edged sword, which brings great challenges while having a positive impact on it. The development of e-commerce mode not only affects the traditional way of trade, but also brings it the opportunity of transformation and innovation. Meanwhile, it also enriches the form of international trade. In order to study the new products of this era, this article will prove the influence of e-commerce on international trade and its development strategies.